FITUR GAMIFIKASI MENINGKATKAN REPURCHASE INTENTION MELALUI CUSTOMER EXPERIENCE DAN CUSTOMER ENGAGEMENT PADA MARKETPLACE - Genta Nugraha Hadi Surya; Kokom Komariah; Resa Nurmala (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the effect of gamification features on Repurchase Inten-tion through Customer experience and customer engagement among marketplace users. This research employed an explanatory quantitative approach using purpos-ive sampling and involved 240 respondents. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that gamification features have a positive and significant effect on Custom-er experience and customer engagement. Furthermore, Customer experience and customer engagement have a positive and significant effect on Repurchase Inten-tion. These findings demonstrate that gamification features can enhance users' Re-purchase Intention through Customer experience and customer engagement devel-oped during marketplace usage.